(untitled) (Research, Society and Development, 2022)
Considering the broad potential of the genus Cymbopogon, here we present a systematic literature survey on it’s antimicrobial potential. This is a review, articles from the Scielo and PubMed platforms. The articles surveyed were published between 2015 and 2020, with the theme of microbiology, including ethnobotanical studies, literature reviews, in vitro, in vivo, reports of clinical trials. Works outside the selected period, duplicate articles, and those only reporting infections of plants by the microorganism were excluded. 98 studies were selected, 74% found in PubMed and 26% in Scielo. Of this total, 21% were ethnobotanical/ethnopharmacology or literature reviews, most of them reporting the use of infusions of the species C. citratus (DC.) Stapf. Moreover, in 57% of the studies, survey respondents did not report antimicrobial use. In relation to 79% of the experimental studies, it was observed that 77% reported total inhibition of microbial growth, 3% indicated moderate growth inhibition, 4% low growth inhibition and 5% reported no inhibition. Among the microbial species analyzed were Escherichia coli, Pseudomonas aeruginosa, Borrelia burgdorferi, Candida albicans, Salmonella enterica and Saccharomyces cerevisiae. In addition, 5% of the articles reported antiviral activity, 5% parasitic control, 1% preventive action against contamination by mesophilic microorganisms. Although the population is not aware of the antimicrobial activity of Cymbopogon sp., studies have demonstrated its antimicrobial potential, thus the extracts of this genus can be an alternative for use in folk medicine as well as a source of new drugs with antimicrobial action.